ANALISIS PENINGKATAN KOMPETENSI SUMBER DAYA MANUSIA DALAM MENGHADAPI ERA 4.0 - PULUNGAN, AHMAD SAYUTI; MAKHRANI, MAKHRANI (LP2MTBM MAKARIOZ, 2023)
Indonesian human resources as assets are required to always develop themselves so that they have the proper competence to compete with other nations. The weaknesses that exist in Indonesian human resources in navigating the current 4.0 era are in terms of skills (soft skills and hard skills), experience, and intellectual abilities, where Indonesian human resources do not have more skills in dealing with the current digital era. Education does not provide thorough preparation for human resourcers in improving skills, both soft skills and hard skills, to face the 4.0 era, so that Indonesian human resourcers lack experience, both work experience and experience in dealing with change or transformation into the 4.0 era. In addition, Indonesian human resources lack high intellectual ability in dealing with change, so Indonesian human resources are still less creative and innovative, so they have not been able to compete with other countries in dealing with change. As a result, some of the human resources who work still do not have competencies that are worthy of being sold worldwide. The research method used is descriptive-quantitative using multiple linear regression analysis using SPSS 22. The population of this study is the workforce in Indonesia, amounting to 128,454 people per person. The sampling technique used in this study is the accidental sampling technique, with a sample size of 100 workers through the distribution of questionnaires conducted by telephone. The results of the study, which are based on the partial hypothesis, state that partially the variables of Human resource skills and experience affect the variables of increasing Indonesian Human resource competencies in the 4.0 era, and simultaneously the variables of Human resource skills, experience and intellectual abilities have a positive and significant effect on increasing Indonesian Human resource competencies in the 4.0 era